Potencial de produção e modelagem da assimilação de carbono para Panicum maximum cv. Mombaça e Brachiaria brizantha cv. Marandu - Santos, Mariely Lopes dos (2016)
Brazilian livestock uses pasture as the basal resource of production systems. Previous knowledge of the characteristics of forage plants and their responses are fundamental for forage planning. It aimed to evaluate physiological responses, modeling of potential carbon assimilation, productive and qualitative characteristics of Brachiaria brizantha cv. Marandu and Panicum maximum cv. Mombaça with or without nitrogen fertilization. The design was a randomized block design in factorial arrangement 2 x 2 (two cultivars: Mombaça and Marandu; unfertilized and fertilized with 550 kg N ha-1 year) in five seasons (Aut/15, winter/15, spring/15, summer/15 e aut/16) with three replications. The experimental period was from March 21 2015 on June 21 2016, including autumn, winter, spring and summer 2015 and autumn 2016 seasons. It was simulated intermittent stocking, by cutting every 28 days and residual height of 15 cm and 40 cm to Marandu and Mombaça. In the summer, fertilized pastures presented higher rates of foliar and canopy photosynthesis with values of 29.8 and 67.21 μmol CO2 m-2 s -1 , respectively. Marandu presented higher leaf photosynthesis rate (23.9 μmol CO2 m-2 s -1 ), in addition to transpiration, stomatal conductance, a, b and total chlorophyll content, as well as greater water use efficiency (2.41 μmol CO2 Mol-1 H2O) under conditions of water stress. However, Mombaça showed higher efficiency in water use (11.89 μmol CO2 mol-1 H2O) when there was water surplus. Nitrogen fertilization increased Marandu and Mombasa herbage accumulation, especially in the summer (7.5 and 13.4 Mg DM/ha), in addition to providing higher CP (20.2%) and reduction of NDF (47,3%) and FDA (21.6%) in prim/15. The greatest annual forage accumulation was verified in fertilized pastures (24.4 Mg/ha.year). It is concluded that nitrogen fertilization is determinant in the intensification of forage production and should be used without any water restriction. In addition, grazing management with the addition of nitrogen should be intensified and adapted according to the season to avoid forage losses due to accelerated growth in the rainy season, especially for Mombaça.